Improving outcomes for care leavers: evaluating a care leaver's assessment of need tool - Wendy Harrington (Scottish Journal of Residential Child Care)
Care leavers' poor outcomes across a range of areas have been well documented since the 1980s. Their vulnerability to homelessness, poor educational achievement, mental ill health and offending (Biehal, Claydon, Stein and Wade,1992; Stein and Wade, 2000; Scottish Executive, 2002a) is well understood but this understanding has not necessarily led to improved practice.